Macro Mineral Content in Five Shrubs Browsed by White-Tailed Deer (Odocoileus virginianus), Northeastern Mexico - Alvarado, María del Socorro; Ramírez Lozano, Roque Gonzalo; González Rodríguez, Humberto; Cantú Silva, Israel; Gómez Meza, Marco Vinicio; Cotera Correa, Mauricio; Jurado Ybarra, Enrique; Domínguez Gómez, Tilo Gustavo (Medwell Journals, 2012)
The Ca, K, Mg, Na and P contents were determined, seasonally during 2 consecutive years in leaves of native browse plants such as Castela erecta Turp sp. Texana (Torr & A. Gray) Cronquist (Simaroubaceae), Celtis pallida Torr. (Ulmaceae), Forestiera angustifolia Torr. (Oleaceae), Lantana macropoda Torr. (Verbenaceae) and Zanthoxylum fagara (L.) Sarg (Rutaceae) that were collected from August 2004 to May 2006 in a semiarid and subtropical area of the State of Nuevo Leon, Mexico at three county (Los Ramones, China and Linares) sites which are grouped under a similar climatic pattern. Mineral contents were measured using an atomic absorption spectrophotometer with exception of P content that was estimated using a colorimeter. All minerals in all species were significantly different among years, sites and seasons and interactions were also significant. In general, plants at Linares site which historically registered the highest rainfall had higher mineral content followed by Los Ramones and China. Moreover, during the 2nd year, all plants species showed higher mineral content than the 1st year. Furthermore, during the Summer session, all plants species had higher mineral content followed by Autumn, Winter and Spring. Regardless of spatio-temporal differences, all plant species had suitable levels of Ca, Mg and K to satisfy range domestic and wild ruminant requirements. In contrast, P and Na contents showed marginal inadequacies in some seasons throughout the year. Seasonal variations in minerals could be associated to climatic conditions like excessive irradiance levels during Summer and extreme low temperatures in Winter and rainfall events.